A Review of Chemotherapy for Locally Advanced Head and Neck Cancers - Larizadeh, Mohammad Hassan; Shabani, Mohammad (Reports of Radiotherapy and Oncology, 2015)
Context: Chemoradiation provides a survival advantage as well as increased rate of organ preservation compared with radiation alone in locally advanced head and neck squamous cell carcinoma (LAHNSCC). Evidence Acquisition: Combined modality protocols can be used in 3 forms: a) induction chemotherapy or neoadjuvant therapy before definitive surgery or radiotherapy, b) Concurrent chemo- radiotherapy, and c) sequential therapy consisting of induction chemotherapy followed by concurrent chemo radiation. Results: Despite an improvement in organ preservation, induction treatment has no impact on survival. Ongoing phase III trials comparing sequential therapy with concurrent chemoradiation may establish which of these two approaches is superior. Conclusions: Until those trials have been completed, Taxane- based sequentional therapy can be a reasonable alternative to concurrent chemo radiotherapy in the patients with locally advanced disease.